Biosorption of 5G blue reactive dye using waste rice husk - Costa Junior, Ismael Laurindo; Finger, Leandro; Quitaiski, Poliana Paula; Neitzke, Samuel Mathias; Besen, Josue Victor; Correa, Maike Krug; Mees, Juliana Bortoli Rodrigues (Eclética Química, 2018)
In this study, the biosorption was used on the removal of 5G blue dye using rice husk residue. Was evaluated the influence of temperature and pH on the biomass pretreated with H3PO4 and NH4Cl. The tests were realized in batch with previous determination of point of zero charge (PZC). Analytical measurements were performed by UV-Vis spectroscopy. It was observed a major influence of pH and temperature on the biosorption capacity of the dye, being the highest removal obtained for the condition of pH 2 and temperature of 50 °C. The time for the biomass-dye system to reach equilibrium was around 45 min. The kinetic model of pseudo-first order adequately represented experimental data and had a good correlation coefficient. In the equilibrium study, it was verified that the Langmuir isotherm was the best fit for the experimental data, with a maximum biosorption capacity of 3,84 mg g-1. The use of rice husk as a biosorbent for the removal of reactive blue 5G dye can be considered promising for the abundance of this residue and the observed sorption capacity